The Great Industrial War Framing Class Conflict in the Media, 1865-1950 - Rondinone, Troy (Rutgers University Press, 2010)
The Great Industrial War, a comprehensive assessment of how class has been interpreted by the media in American history, documents the rise and fall of a frightening concept: industrial war. Moving beyond the standard account of labor conflict as struggles between workers and management, Troy Rondinone asks why Americans viewed big strikes as "battles" in "irrepressible conflict" between the armies of capital and laborùa terrifying clash between workers, strikebreakers, police, and soldiers. Examining how the mainstream press along with the writings of a select group of influential reformers and politicians framed strike news, Rondinone argues that the Civil War, coming on the cusp of a revolution in industrial productivity, offered a gruesome, indelible model for national conflict. He follows the heated discourse on class war through the nineteenth century until its general dissipation in the mid-twentieth century. Incorporating labor history, cultural studies, linguistic anthropology, and sociology, The Great Industrial War explores the influence of historical experience on popular perceptions of social order and class conflict and provides a reinterpretation of the origins and meaning of the Taft-Hartley Act and the industrial relations regime it supported.
Keywords: History; History; Social conflict; Labor disputes; United States; dept.his; faculty_collection